Scientific Socialism; A Panacea For Poor Leadership Situation In Nigeria - Isenyo Solomon Ogaba; Abraham Lubem Abado (Universitas Negeri Makassar, 2021)
Humans are significantly inconsequential, socio-political, paranormal entities with gregarious natural impulses that are polymorphously perversed. Going by human natural quest, to live with one another in harmony within a space (State), it becomes exigent for human unpredictable nature to be properly regulated for peace to prevail. Unfortunately, the Nigerian State is faced with serious leadership challenges as witnessed in every sphere of Her nation. This paper observed that humans by nature are inherently corrupt, and the need for the use of formidable force (Scientific Socialism) to regulate every sphere of society cannot be overemphasized. Hence, the paper through the historical dialectical method uncovered that other forms of socialist ideology are good; however, Marx's scientific socialist ideology is more efficacious in bringing about a more radical revolutionary change that could overhaul the entire socio-political scheme of things in a contemporary Nigerian leadership situation.